Analisis Pengaruh Komponen Indeks Pembangunan Manusia terhadap Pertumbuhan Ekonomi di Indonesia Tahun 2014 – 2018 - Arfita, Aurellia Puteri (Regress: Journal of Economics & Management, 2023)
Human capital plays a crucial role in productivity within economic growth. The development of human capital can be measured by the Human Development Index (HDI), an indicator to gauge the potential of Human Resources (HR) from various aspects The available capital in Indonesia to compete with fellow ASEAN nations remains significantly restricted, particularly when it comes to the international level. Indonesia's capital for competing with other ASEAN countries remain considerably low, even more so when competing on a global level. To measure the extent of the relationship between human capital and economic growth in Indonesia, the Human Capital Augmented Solow Growth Model was adopted to determine the interdependence of capital stock, labour, and technology on the total output of goods and services. This study uses panel data from three components in the HDI, namely health, education, and a decent standard of living from 2014-2018 in 34 provinces in Indonesia from the Central Statistics Agency (BPS). Based on the research findings using panel data regression, all HDI components significantly influence the Gross Regional Domestic Product (GRDP), thus proving that human capital, as measured by HDI components, has an impact on economic growth. Life expectancy and years of schooling have a negative correlation with GRDP, while average years of schooling and per capita expenditure exhibit a positive correlation with GRDP.